Depression among Patients with Chronic Viral Hepatitis Attending Tertiary Level Hospital - Nebina Piya,; Gachhadar, Rashmi; Shrestha , Rupesh; Ale, Manu (Journal of College of Medical Sciences-Nepal, 2025)
Background Chronic viral hepatitis is a major public health problem worldwide. Patients with chronic viral hepatitis face both physical and mental problems. So, this study aimed to determine the prevalence of depression among patients with chronic viral hepatitis. Methods A cross-sectional analytical study was conducted at the outpatient department of hepatology unit of Bir Hospital. Consecutive sampling technique was used. Total sample size was 208. Pretesting was conducted in 10% of the total sample size. The research tool consisted of two parts, Part A consisted of information related to socio-demographic and economic characteristics and disease related information and Part B consisted of Beck Depression Inventory 1 a. Data were analysed using descriptive statistics like frequency, percentage, mean, standard deviation, median and inferential statistics like chi square and multiple logistic regression. Results Less than half (38.9%) of the respondents belonged to age group 25-40 years. Less than half (43.8%) had completed secondary level education. Around 1/3rd (35.1%) of the respondents belong to upper middle so- cio-economic class. Majority (87.9%) of the respondents were diagnosed with Hepatitis B. Less than 1/4th (15.4%) of the respondents had moderate depression with the need for mental health intervention. Age, religion, ethnicity, socioeconomic status, types of hepatitis and duration of diagnosis were significantly as- sociated with depression. Multivariable model shows ethnicity, socio-economic status, type of hepatitis and duration of diagnosis as the predictors of depression. Conclusions Despite of the lower prevalence of depression among the patients with chronic hepatitis, it is crucial to address mental health dimension while treating the patients and implement mental health interventions among those with different severity of depression.